INFLUENCE OF PHYSICO-CHIMICAL PARAMETERS ON ZOOPLANKTON DISTRIBUTION IN FOUM EL-KHANGA DAM IN SOUK-AHRAS - Bendjebbar Aymen; Hamdi Ghada (My University, 2024)
The identification of freshwater microalgae is a very complex process that involves the use of several different techniques to determine the composition and structure of algae, including optical microscopy, scanning electron microscopy, liquid chromatography and infrared spectroscopy to determine the shape, size, structure and chemical composition of algae. The aim of our study is to study the factors that would help in the emergence of zooplankton in the dam of Foum El Khenga "Oued Charef" of Zouabi municipality by studying the physicochemical characteristics of the dam water and identifying the types of zooplankton based on their cell counts. During the period from March to April of 2024 at three stations, the results of physical and chemical analyses of Foum El Khenga dam water at the three stations showed seasonal differences in temperature, pH, and water transmissivity factor was high in April and low in March, we also observed clarity in the dam water (NTU less than 5), while the results of sodium and phosphate were low throughout the study period and are lower than the Algerian standards. As for the results of zooplankton identification, the results of the study showed that Foum El-Khanga dam includes fifteen species belonging to five categories (Les rotifères, les copépodes, les cladocères, les coccobaciles and les schistosomes). -------------------------------------------------------------------------------------------------------------------------------- إن عملية تحديد الطحالب الدقيقة للمياه العذبة هي عملية جد معقدة تتضمن استخدام عدة تقنيات مختلفة لمعرفة و تحديد تركيب وتكوين الطحالب من بينها الفحص المجهري البصري والمسح المجهري الإلكتروني والكروماتوغرافيا السائلة والتحليل الطيفي للأشعة تحت الحمراء التي تعمل على تحديد شكل ، حجم و بنية الطحالب وتكوينها الكيميائي إن الهدف من دراستنا هو دراسة العوامل التي من شأنها تساعد في ظهور العوالق الحيوانية في سد فم الخنجة "واد شارف" لبلدية الزوابي من خلال دراسة الخصائص الفيزيوكيميائية لمياه السد وكذا تحديد انواع العوالق الحيوانية بناءا على احصاء خلاياها خلال فترة من مارس إلى أفريل من 2024 في ثلاث محطات اظهرت نتائج التحاليل الفيزيائية والكيميائية لمياه سد فم الخنجة على مستوى المحطات الثلاثة اختلافات موسمية في درجة الحرارة، درجة حموضة قاعدية، و عامل ناقلية الماء كان مرتفعا في شهر أفريل و منخفضا في مارس كما لاحظنا صفاء في مياه السدNTU)أقل من 5) اما بالنسبة لنتائج الصديوم و الفسفات فكانا منخفضين طيلة فترة الدراسة و هي اقل من المعايير الجزائرية اما فيما يخص نتائج تحديد العوالق الحيوانية لقد اظهرت نتائج الدراسة أن سد فم الخنجة يضم خمسة عشر نوع تنتمي الى خمس فئات (Les rotifères, les copépodes, les cladocères, les coccobaciles et les schistosomes) --------------------------------------------------------------------------------------------------------------------------------- L'identification des microalgues d'eau douce est un processus très complexe qui implique l'utilisation de plusieurs techniques différentes pour déterminer la composition et la structure des algues, y compris la microscopie optique, la microscopie électronique à balayage, la chromatographie liquide et la spectroscopie infrarouge pour déterminer la forme, la taille, la structure et la composition chimique des algues. Le but de notre étude est d'étudier les facteurs qui favoriseraient l'émergence du zooplancton dans le barrage de Foum El Khenga "Oued Charef" de la commune de Zouabi en étudiant les caractéristiques physico-chimiques de l'eau du barrage et en identifiant les types de zooplancton sur la base de leur nombre de cellules. Durant la période allant de mars à avril 2024 au niveau de trois stations, les résultats des analyses physico-chimiques de l'eau du barrage Foum El Khengaau niveau des trois stations ont montré des différences saisonnières au niveau de la température, du pH, et le facteur de transmissivité de l'eau était élevé en avril et faible en mars, nous avons également observé une clarté de l'eau du barrage (NTU inférieur à 5), alors que les résultats du sodium et du phosphate ont été faibles tout au long de la période d'étude et sont inférieurs aux normes Algériennes. Quant aux résultats de l'identification du zooplancton, les résultats de l'étude ont montré que le barrage de Foum El Khengacomprend quinze espèces appartenant à cinq catégories (Les rotifères, les copépodes, les cladocères, les coccobaciles et les schistosomes).